Analisis dan Perancangan Sistem Informasi Pemesanan Barang (Studi Kasus: PT. Trivia Nusantara) - Afifahlya Alif Rizyomi; Mochamad Chandra Saputra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Trivia Nusantara is a business in advertising and retail of office stationery. After doing an observation, there is a problem in ordering products process. Which lack of information system support causes the process of ordering products to be longer and takes a lot of cost in communication. Growth of technology impact on the increasingly business competition, this trigger PT. Trivia Nusantara to build an information system in order to support the company's operations. Due to PT. Trivia Nusantara also does not have an IT expert so the company's leader plans to build an information system by working with vendors. Based on the concept of SDLC (Software Development Life Cycle) the initial thing required is a documented requirements analysis and system design. Analysis and design performed using Ripple methodology in the initial 4 phases. Genesis phase and requirement phase used to requirements analysis. While the system design in the analysis phase and design phase. The importance of evaluating the requirements in this study using 2 evaluation, consistency analysis and correctness. In consistency analysis method proved have a 100% percentage value consistent. And the correctness test proving that system requirements with system design is include in correctness category.